Detecting the Sybil Attack in Wireless Sensor Network :Survey - Pramod, A.V; Azeem, Md. Abdul; Prakash, M. Om (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Mobility is frequently a problem for providing security servicesÂ  in ad hoc networks. In this paper, we render that mobility can alsobe used to enhance security. Specifically, we render that nodes which are in Â passively monitor traffic in the network can able to detect a Sybil attacker which uses a number of network identities simultaneously. We can do through simulation that this detection can be done by a single node, or multiple trusted nodes can join to improve the accuracy of detection. We then show that although the detection mechanism will falsely identify groups of nodes traveling together as a Sybil attacker, we can extend the protocol to monitor collisions at the MAC level to differentiate between a single attacker spoofing many addresses and a group of nodes traveling in close proximity.